Isobolographic Analysis of the Cytoprotective Effect of Dapsone and Cannabidiol Alone or Combination upon Oxygen-Glucose Deprivation/Reoxygenation Model in SH-SY5Y Cells - Marcela Islas-Cortez; Camilo Ríos; Jorge Manzanares; Araceli Díaz-Ruiz; Ricardo Pérez- (MDPI AG, 2024)
Oxidative stress and apoptosis cell death are critical secondary damage mechanisms that lead to losing neighboring healthy tissue after cerebral ischemia. This study aims to characterize the type of interaction between dapsone (DDS) and cannabidiol (CBD) and its cytoprotective effect in an in vitro model of oxygen and glucose deprivation for 6 h followed by 24 h of reoxygenation (OGD/R), using the SH-SY5Y cell line. For the combined concentrations, an isobolographic study was designed to determine the optimal concentration-response combinations. Cell viability was evaluated by measuring the lactate dehydrogenase (LDH) release and 3-[4, 5-dimethyl-2-thiazolyl]-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assays. Also, the reactive oxygen species (ROS) and reduced glutathione (GSH) levels were analyzed as oxidative stress markers. Finally, caspase-3 activity was evaluated as a marker cell death by apoptosis. The results showed a decrease in cell viability, an increase in oxidant stress, and the activity of caspase-3 by the effect of OGD/R. Meanwhile, both DDS and CBD demonstrated antioxidant, antiapoptotic, and cytoprotective effects in a concentration-response manner. The isobolographic study indicated that the concentration of 2.5 µM of DDS plus 0.05 µM of CBD presented a synergistic effect so that in treatment, cell death due to OGD/R decreased. The findings indicate that DDS-CBD combined treatment may be a helpful therapy in cerebral ischemia with reperfusion.